2020
DOI: 10.1002/ana.25989
|View full text |Cite
|
Sign up to set email alerts
|

Statewide Emergency Medical Services Protocols for Status Epilepticus Management

Abstract: Although seizures are common in prehospital settings, standardized emergency medical services (EMS) treatment algorithms do not exist nationally. We examined nationwide variability in status epilepticus treatment by analyzing 33 publicly available statewide EMS protocols. All adult protocols recommend intravenous benzodiazepines (midazolam, n = 33; lorazepam, n = 23; diazepam, n = 24), 30 recommend intramuscular benzodiazepines (midazolam, n = 30; lorazepam, n = 8; diazepam, n = 3), and 27 recommend intranasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Equally, a recent randomized controlled trial has shown that intubation after 2 of 12 established SE is independent of baseline characteristics and early neurologic recovery, though it is strongly associated with site-specific practice pattern variation [8]. Additionally, a recent study showed high variability of SE treatment in EMS algorithms in the US [9]. The systematic priority-based emergency assessment of Airway, Breathing, Circulation, Disability, and Exposure (i.e., ABCDE approach) is the standard examination of critically ill patients as recommended by international organizations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, a recent randomized controlled trial has shown that intubation after 2 of 12 established SE is independent of baseline characteristics and early neurologic recovery, though it is strongly associated with site-specific practice pattern variation [8]. Additionally, a recent study showed high variability of SE treatment in EMS algorithms in the US [9]. The systematic priority-based emergency assessment of Airway, Breathing, Circulation, Disability, and Exposure (i.e., ABCDE approach) is the standard examination of critically ill patients as recommended by international organizations [10,11].…”
Section: Introductionmentioning
confidence: 99%